Irrigation and FYM effect on seed, oil and carvone yield and economics of European dill (Anethum graveolens) - VINEETA, VINEETA; SHARMA, U C; VANDANA, VANDANA; GUPTA, ATUL K; SRIVASTAVA, D S (The Indian Journal of Agricultural Sciences, 2013)
European dill (Anethum graveolens L.) has been used in ayurvedic medicines since ancient times and it is a popularherb widely used as a spice and also yields essential oil. A field cum laboratory experiment was conducted for three years from 2005–08 at Norman E Borlaug Crop Research Centre and in the Department of Agronomy of GBPUA & T, Pantnagar (Uttarakhand) to study the effect of irrigation and FYM on yield and oil quality of European dill. The treatments comprising 4 CPE levels of irrigation (50, 100, 150 and 200 mm) and 3 fertility levels (0, 15 and 30 tonnes FYM/ha) were laid out in factorial randomized block design with 3 replications. Various growth and yield attributes were found to be significantly higher due to irrigation at 100 mm CPE and fertilized with 30 tonnes FYM/ha (I100F30). This caused significant enhancement in the seed, oil and carvone yield and finally highest net return (Rupees,36 145/ha) and B: C ratio (1.57).